A rare Lisfranc-type injury involving dorsal dislocation of the intermediate cuneiform. (29th July 2014) - Kalraiya, Ashish Jain; Vanhegan, Ivor; Cheung, Alan; Rudge, Ben
Abstract : Lisfranc injuries occur at the tarsometatarsal joint resulting from direct or indirect force to the midfoot. They account for only 0.2% of all fractures, with diagnoses easily missed on presentation. The resultant instability is often associated with significant morbidity to the patient. This report describes a Lisfranc injury sustained by a healthy gentleman who suffered indirect trauma to the foot when he fell from a standing height. Plain film radiographs and CT revealed dorsal dislocation of the intermediate cuneiform associated with fractures at the base of the third and fourth metatarsals. He underwent open reduction and internal fixation the following day. His Foot and Ankle Disability Index (FADI) score improved from 16.3 1 week postoperatively to 58.7 6 months postoperatively. This report describes a rare injury pattern resulting from indirect, low-energy trauma. We provide a guide to appropriate radiological imaging and evaluation in the assessment of these complex injuries.